2022
DOI: 10.1038/s41431-021-01013-6
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Inherited Neoplasia Allele Syndrome (MINAS): an update

Abstract: Multi-locus Inherited Neoplasia Allele Syndrome (MINAS) refers to individuals with germline pathogenic variants in two or more cancer susceptibility genes(CSGs). With increased use of exome/genome sequencing it would be predicted that detection of MINAS would become more frequent. Here we review recent progress in knowledge of MINAS. A systematic literature search for reports of individuals with germline pathogenic variants in 2 or more of 94 CSGs was performed. In addition, participants with multiple primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 30 publications
1
30
0
1
Order By: Relevance
“…Multi-locus inherited neoplasia allele syndrome (MINAS) is a relatively new entity that was initially reported in BRCA1 / BRCA2 -related cancers ( 21 ). With increasing adoption of next generation sequencing technologies for cancer susceptibility germline (CSG) testing, there has been a rise in reports of non- BRCA1 / BRCA2 related MINAS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Multi-locus inherited neoplasia allele syndrome (MINAS) is a relatively new entity that was initially reported in BRCA1 / BRCA2 -related cancers ( 21 ). With increasing adoption of next generation sequencing technologies for cancer susceptibility germline (CSG) testing, there has been a rise in reports of non- BRCA1 / BRCA2 related MINAS.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by McGuigan et al. reported that atypical tumor phenotypes comprised of about 15% of non- BRCA1 / BRCA2 MINAS cases, which could be secondary to complex interactions between the relevant CSGs ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multi-locus inherited neoplasia allele syndrome (MINAS) is an example of this. Individuals can develop multiple neoplasms because they have pathogenic variants in multiple cancer genes [6]. In turn, polygenic risk, as measured by cancer-associated SNPs from Genome-Wide Association Studies (GWAS) has a role in modifying cancer risk.…”
mentioning
confidence: 99%